Cooperation between HDAC3 and DAX1 mediates lineage restriction of embryonic stem cells. (28th April 2021) - Olivieri, Daniel; Castelli, Eleonora; Kawamura, Yumiko K; Papasaikas, Panagiotis; Lukonin, Ilya; Rittirsch, Melanie; Hess, Daniel; Smallwood, Sébastien A; Stadler, Michael B; Peters, Antoine H F M; Betschinger, Joerg
Abstract: Mouse embryonic stem cells (mESCs) are biased toward producing embryonic rather than extraembryonic endoderm fates. Here, we identify the mechanism of this barrier and report that the histone deacetylase Hdac3 and the transcriptional corepressor Dax1 cooperatively limit the lineage repertoire of mESCs by silencing an enhancer of the extraembryonic endoderm‐specifying transcription factor Gata6. This restriction is opposed by the pluripotency transcription factors Nr5a2 and Esrrb, which promote cell type conversion. Perturbation of the barrier extends mESC potency and allows formation of 3D spheroids that mimic the spatial segregation of embryonic epiblast and extraembryonic endoderm in early embryos. Overall, this study shows that transcriptional repressors stabilize pluripotency by biasing the equilibrium between embryonic and extraembryonic lineages that is hardwired into the mESC transcriptional network. Synopsis: Embryonic stem cells (ESC) predominantly differentiate into epiblast‐like fate as opposed to extraembryonic endoderm, but the molecular mechanism underlying this early developmental preference remains ill‐defined. Using multi‐layered expression profiling, this study identifies histone deacetylase Hdac3 and transcriptional corepressor Dax1 as key determinants of lineage barriers in mouse ESCs. Depletion of Hdac3 or Dax1 increases GATA6‐dependent primitive endoderm (PrE) formation at metastable serum/LIF conditions. Dax1 inhibits mESC transdifferentiation by controlling nuclear receptor Nr5a2 activity. Hdac3 acts with corepressors Ncor1/2 to target a single enhancer upstream of the PrE‐specifying transcription factor gene Gata6 . Hdac3 or Dax1 mutant mESCs give rise to bona fide PrE in blastocysts. Abstract : Extraembryonic transdifferentiation of ESCs is controlled by collaborative activity of transcriptional repressors.